(untitled) (CIPEEX, 2025)
This document discusses the development of a bot designed for appointment confirmations, which aims to streamline administrative tasks within a clinic. The primary focus of the project is on automation to enhance efficiency by sending messages to patients prior to their appointments. This process significantly reduces the workload of the secretary, who currently spends considerable time managing these communications. The bot functions by automatically delivering confirmation messages, thereby eliminating the need for manual intervention. The employee’s role transitions to verifying the accuracy of the information contained in the messages before authorizing the bot to send them to the appropriate contacts. This automation is anticipated to improve the overall patient experience, decrease the burden on the administrative team, and contribute to better organizational practices within the clinic. By allowing the secretary to concentrate on other critical tasks, the bot enhances operational efficiency and ensures that patients remain informed about their scheduled appointments. Overall, this initiative represents a significant step toward optimizing clinic workflows.